Upaya perbaikan Hasil belajar Sisw Kelas V Menggunakan Model Kooperatif Tipe Course Review Horay - fitrimawati, ayu; fitria, yanti; hamimah, hamimah (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This research is conducted by the low learning outcomes in social science of the fifth grade students of  SD Negeri 14 Bayang. This is cavsed by the learning still use “teacher centre” in the classroom. The purpose of this study is to improve learning outcomes by using cooperative model “Course Review Horay” type in social science learning. The type of reserch is a classroom action research with teacher and students as subjects of research. The finding showesd that the implementation of teacher activity in 1th sycle, the average is 76%, in 2nd cyle the average 95%. The assessment of implementation of students activity in 1st cycle, the average is 71% and in 2nd cycle, the average is 82%. This it can be concluded that the application of cooperatif model Course Review Horay type in social science learning can improve students learning outcomes. Keywords: Learning Outcomes, Cooperative Model CRH